Fractional Exhaled Nitric Oxide as an Inflammatory Biomarker in Chronic Obstructive Pulmonary Disease (COPD) with or without Concurrent Diagnosis of Asthma: The Canadian Cohort Obstructive Lung Disease (CanCOLD). (5th July 2020) - Mostafavi-Pour-Manshadi, Seyed-Mohammad-Yousof; Naderi, Nafiseh; Mancino, Palmina; Li, Pei Zhi; Tan, Wan; Bourbeau, Jean
Abstract: We studied whether fractional exhaled nitric oxide ( F ENO ) can differentiate chronic obstructive pulmonary disease (COPD) with concurrent diagnosis of asthma from COPD-only as well as its ability to predict disease severity and progression. This study was embedded in the Canadian Cohort Obstructive Lung Disease (CanCOLD). Subjects of ≥40 years old completed F ENO measurements were subdivided into four groups, including COPD ( N = 86 [COPD-only ( N = 35) and COPD with concurrent diagnosis of asthma ( N = 51)], healthy ( N = 72), and at risk ( N = 151). Three of the most common clinical definitions were used for characterizing COPD with concurrent diagnosis of asthma: 1) atopy and self-reported physician diagnosis of asthma, 2) ≥12% and ≥200 ml post-bronchodilator FEV1; 3) self-reported physician diagnosis of asthma. F ENO values were classified using quartiles and the American Thoracic Society (ATS) guideline 2011. Compared to COPD-only, more COPD with concurrent diagnosis of asthma had a significant F ENO50 level of ≥ 33.5 ppb (fourth quartile) than COPD-only ( p = 0.045, 0.011, and 0.006, for definition 1, 2, and 3, respectively). Considering the ATS guideline 2011, fewer COPD with concurrent diagnosis of asthma had F ENO50 < 25 than COPD-only, which was statistically significant with definition 1 and 3 ( p = 0.038 and 0.026, respectively). F ENO as a biomarker has the potential to be used as a complementary value for differentiating COPD with concurrent diagnosis of asthma from COPD-only. Further studies should be conducted on validated definitions of COPD with concurrent diagnosis of asthma, which may include a reference to the type of airway inflammation in addition to the clinical definition.